A qualitative study exploring pupil and school staff perceptions of school meal provision in England. Issue 9 (2nd September 2015) - Day, Rhiannon E.; Sahota, Pinki; Christian, Meaghan S.; Cocks, Kim
Abstract: Despite recent attempts to improve the quality of school meals in England through the introduction of school meal standards, uptake remains low. Since the introduction of the universal infant free school meal (UIFSM) scheme in September 2014 all pupils in Reception, Year 1 and Year 2 in English state-funded primary schools are eligible to receive a free lunch. This study aimed to explore the perceptions of pupils, catering managers and head teachers concerning school meal provision in eight primary schools in North England and provides a unique insight into each school's preparation for implementation of UIFSM. A total of thirty-two focus groups were conducted with sixty-four pupils aged 7–8 years (Year 3) and sixty-four pupils aged 9–10 years (Year 5) in June–July 2014, to explore perceptions of school meals. Interviews were carried out with six catering managers and five head teachers concerning catering and the impending implementation of UIFSM. Increasing acceptance of school meals could lead to improved uptake. Pupils desired increased choice and menu variety, including greater variety of vegetables and fruit. Caterers can influence the quantity and types of foods offered to pupils, and there are opportunities for them to promote healthy eating behaviours in the dining room. The important roles of school meal providers, caterers, pupils and parents need to be recognised to improve delivery and acceptability of school meals and ultimately school meal uptake. There were practical challenges to implementation of UIFSM, with some concerns expressed over its feasibility. Head teachers were mainly positive about the potential beneficial impacts of the scheme.